2021
DOI: 10.3390/ijerph18179008
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Adversity: Resilience Dynamics of Livestock Farmers in Two Agroecological Zones of Ghana

Abstract: Despite the increasing occurrence of adverse events including droughts and conflicts, livestock farmers in Ghana continue to raise animals to support their livelihoods and the national economy. We assessed the resilience of cattle farmers (CF) to adverse events they faced using a cross-sectional survey of 287 CF in two agroecological zones in Ghana. Resilience to adversities was assessed using the Resilience Scale (RS-14). Resilience scores and categories were computed and factors that explained variations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These ndings are intuitive, as previous research among sections of the target population, showed animal diseases as the major bottleneck to the productivity and wellbeing of cattle farming households, as well as the use of self-treatment and sale of diseased animals by farmers as a coping strategy to deal with the lack of adequate veterinary services (12,22,27). The discordance between the perceived effects of the adverse events on livestock production between the farmers and their VOs was logical, given the reported shortfalls in the veterinary workforce and service delivery to livestock farmers in Ghana (13).…”
Section: Discussionmentioning
confidence: 58%
“…These ndings are intuitive, as previous research among sections of the target population, showed animal diseases as the major bottleneck to the productivity and wellbeing of cattle farming households, as well as the use of self-treatment and sale of diseased animals by farmers as a coping strategy to deal with the lack of adequate veterinary services (12,22,27). The discordance between the perceived effects of the adverse events on livestock production between the farmers and their VOs was logical, given the reported shortfalls in the veterinary workforce and service delivery to livestock farmers in Ghana (13).…”
Section: Discussionmentioning
confidence: 58%
“…In Ghana, Nuvey et al (2021) also assessed how livestock integration or mixed farming influences household resilience among 287 sampled smallholders in the Bunkpurugu-Yunyoo and Kwahu Afram Plains South districts. Their sample involved 142 and 145 households that integrated the rearing of cattle in the farming system in the Bunkpurugu-Yunyoo and Kwahu Afram Plains South districts, respectively.…”
Section: Livestock Integrationmentioning
confidence: 99%